The Journal of Rhetorical Pattern in Journalistic Language - Riahmawani Purba (State University of Medan, 2013)
ABSTRACT This study deals with the analysis of the rhetorical pattern in journalistic language using the style of the inverted-pyramid, they are Who, What, Why, When, Where, and How. The purpose of this study was to find out the dominant rhetorical pattern that was used in a news. The method of this study was descriptive quantitative design. The data for this study were collected from fifteen selected articles about corruption in Indonesia in an English daily newspaper, The Jakarta Post. Fifteen articles were taken from The Jakarta Post in the year 2011, from August until December. This study concludes with findings and implication.